Promotion and Dissemination of Small-scale Renewable Energy Technologies and Its Implication on Sustainable Forest Management: Lesson from Ethiopia - Belachew, Azmera; Kaba, Gemechu; Megersa, Shasho (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Small-scale renewable energy technologies (RETs), such as improved cook stoves (ICS), solar power, and biogas, are recognized as crucial for mitigating deforestation and greenhouse gas emissions. While various organizations have distributed these RETs throughout Ethiopia for diverse purposes, limited evidence exists on their actual impact and the challenges hindering widespread adoption. This paper reviews existing research and key informant interviews to identify both the contributions and barriers specific to these RETs. The findings demonstrate that promoting selected RETs significantly decreases household biomass consumption, which in turn lowers forest degradation and greenhouse gas emissions. Specifically, using ICS and biogas technologies can reduce annual carbon dioxide equivalent emissions by 0.56 to 5.67 million tons and wood fuel consumption by 0.3 to 3.1 million tons. However, the potential wood fuel savings from currently disseminated biogas plants and ICS offset less than 7.2% of Ethiopia's overall annual biomass energy demand. Several obstacles impede the broader adoption of RETs, including technical, financial, market, institutional, and infrastructural limitations. This study suggests that greater sector integration, robust financial institutions, capacity-building centers, active community engagement, and the development of renewable energy sources are essential for wider dissemination of RETs.